The transformation of work? A quantitative evaluation of changes in work in Portugal - Moniz, António Brandão (2008)
This report is made for the Work Package 15 of WORKS project and tries to develop more information on the Portuguese situation in the work structures changes in the recent years. It starts with an analysis of socio- economical indicators (Macro economical indicators, Employment indicators, Consumption, Technology at the workplace, Productivity), and then approaches the situation in terms of work flexibility in its dimensions of time use and New forms of work organisation. It traces employment in business functions with a sectoral and occupational approach, and analyses the occupational change in South Europe with particular relevance to Portugal (skill utilisation and job satisfaction, occupational and industrial mobility, quantitative evaluation of the shape of employment in Europe. Finaly are analysed the globalisation indicators.